Rap: o duelo de rimas no cotidiano do jovem - Tejera, Daniel Bidia Olmedo [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This research will focus on the “Batalha Central”, an event that happens every month at downtown of Piracicaba / SP in which admirers of Hip-hop culture and Rap music come together to fight duels rhymes in a playful way. The objective of this study is to identify if the Hip-hop – specifically Rap battles in the context of improvisation – may or may not can contribute to development of the participant, especially critical and creative and to check the influence cultural precepts of the Hip-hop can have on participants. The Hip-hop emerges from an urban context, created by young blacks and caribbean immigrants as a form of cultural expression, in the district of the Bronx, New York, United States in the 60s. In order to transform the gang violence in disputes healthy, Afrika Bambaataa – one of the main organizers of block parties – began to organize such parties aiming to convert the strife in duels involving artistic expressions divided into four elements: Mc, Dj, Break and Graphite. The merger between the Mc and Dj Rap originated. The type of Rap that we discuss in this study is the impromptu Rap, sort of challenge based on oral poetry and improvisation, a mechanism similar to that found in brazilian “Repente”. This is a qualitative research is characterized by a case study and exploration. To obtain data, were used for semistructured interviews, document analysis and participant observation, in addition to a previous literature. Through this study it was possible to understand the influence exerted by the precepts of Hip-hop in the lives of young people participating in this leisure practice, which will probably end up supplying some needs unmet at school, or other follow-up of society, in addition to understanding a little about how specifically the battles of Mc `s interferes with the development of creativity and criticality of the practitioner

Este trabalho versará sobre a Batalha Central, evento que acontece mensalmente, no centro de Piracicaba/SP em que admiradores da cultura Hip-hop e da música Rap se reúnem, para travar duelos de rimas de uma forma lúdica. O objetivo deste trabalho é identificar se o Hip-hop – especificamente o Rap no contexto das batalhas de improviso – pode ou não contribuir para o desenvolvimento do participante, principalmente crítico e criativo, além de verificar a influência de ordem cultural que os preceitos do Hip-hop podem exercer nessas pessoas. O Hiphop emerge de um contexto urbano, criado por jovens negros e imigrantes caribenhos como uma forma de expressão cultural, no distrito do Bronx, Nova Iorque, Estados Unidos, na década de 60. A fim de transformar a violência das gangues em disputas sadias, Afrika Bambaataa – um dos principais organizadores das festas de rua – passou a organizar tais festas, objetivando converter as “rixas” em duelos que envolviam expressões artísticas, divididas em quatros elementos: Mc, Dj, Break e Grafite. A fusão entre o Mc e o Dj originou o Rap. A modalidade de Rap que abordaremos nesse estudo é o Rap de improviso, espécie de poesia oral, baseada no desafio e improviso, mecanismos parecidos com os encontrados no Repente. Esta é uma pesquisa qualitativa caracterizada por ser um estudo de caso e exploratório. Para a obtenção de dados, foram usadas a entrevista semiestruturada, a análise documental e a observação participante, além de um prévio levantamento bibliográfico. Através deste estudo, foi possível perceber a influência exercida pelos preceitos do Hip-hop na vida dos jovens participantes desta prática de lazer, que acaba suprindo algumas necessidades provavelmente não satisfeitas na escola ou em outro seguimento da sociedade, além de entender como especificamente as batalhas de Mc`s interferem no desenvolvimento da criatividade e criticidade do praticante, e consequentemente...
Keywords: Educational sociology; Sociologia educacional; Rap (Música); Improvisação (Musica); Rimas; Hip-hop (Cultura popular); Jovens; Criatividade; Piracicaba (SP)